DABCO‐promoted Diaryl Thioether Formation by Metal‐catalyzed Coupling of Sodium Sulfinates and Aryl Iodides. Issue 12 (19th April 2020) - Liu, Yanpeng; Lam, Long Yin; Ye, Jiqing; Blanchard, Nicolas; Ma, Cong
Abstract: A scalable catalytic synthesis method using commodity chemicals for constructing diaryl thioethers directly from sodium arylsulfinates and iodoarenes is reported in this study. In the presence of CuO or other copper salts such as Cu(OAc)2 as well as palladium catalysts, DABCO demonstrated to be essential to promote this transformation. Various iodoarenes and aryl sulfinates were examined and demonstrated the viability of this method. The mechanistic study showed that radical reactions occurred, while DABCO N ‐oxide radical can be observed by mass spectrometry. A plausible catalytic mechanism involving DABCO is also discussed, suggesting synergistic reduction of sulfinate by Cu(II) and DABCO is the key step of this coupling reaction. Abstract :